The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1093/geront/gnz053
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Staff Time and Care Quality in Long-Term Care Facilities: A Systematic Review

Abstract: Background and Objectives In long-term care (LTC) facilities, nursing staff are important contributors to resident care and well-being. Despite this, the relationships between nursing staff coverage, care hours, and quality of resident care in LTC facilities are not well understood and have implications for policy-makers. This systematic review summarizes current evidence on the relationship between nursing staff coverage, care hours, and quality of resident care in LTC facilities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…Several studies have shown inverse relations between staffing levels and care hours, and poor outcomes such as rates of infection and hospital admission among residents. [18][19][20][21] Recent studies have also shown an association between low staffing levels and COVID-19 infections within LTC homes. [22][23][24] Many LTC staff, in particular care aides or personal support workers, are underpaid and less likely to secure fulltime positions relative to their counterparts in other sectors of the health care system.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown inverse relations between staffing levels and care hours, and poor outcomes such as rates of infection and hospital admission among residents. [18][19][20][21] Recent studies have also shown an association between low staffing levels and COVID-19 infections within LTC homes. [22][23][24] Many LTC staff, in particular care aides or personal support workers, are underpaid and less likely to secure fulltime positions relative to their counterparts in other sectors of the health care system.…”
Section: Discussionmentioning
confidence: 99%
“…While we did not conduct systematic reviews to assess whether each of the identified research priorities have been addressed before, TREC researchers with extensive expertise in the content area of prioritized research questions have identified that the identified priorities indeed not only constitute a gap in using our TREC data, but also a gap in the literature. For example, the question identified as highest priority (influence of different staffing levels and staff mix on resident outcomes) has been addressed in LTC settings [35,36], but these reviews highlight that the quality of available studies is weak, findings are heterogeneous and inconclusive, and that especially the interaction between elements of care staff work environments (leadership, culture, connections within the team) and staffing levels or staff mix may better explain resident outcomes. However, this interaction has not been studied yet in LTC.…”
Section: Discussionmentioning
confidence: 99%
“…There have been, however, no systematic reviews that investigate a minimum HPRD of RNs to attain the maximum quality of care in NHs [ 22 ]. Most studies used cross-sectional or retrospective designs [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been, however, no systematic reviews that investigate a minimum HPRD of RNs to attain the maximum quality of care in NHs [ 22 ]. Most studies used cross-sectional or retrospective designs [ 22 ]. In a systematic review (54 studies in total), 20 (37%) were retrospective studies, 16 (30%) were retrospective studies with cross-sectional analysis, and nine (17%) used cross-sectional analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation